Contraceptive behaviors and media influence among women in Bangladesh: exploring the effects of age and education - Moon, Monira Parvin (Frontiers in Global Women's Health, 2025)
BackgroundMarried Bangladeshi women of reproductive age have improved their contraceptive use in recent decades. This review study searched PubMed, Scopus, and Google Scholar to examine how age and education affect Bangladeshi women's contraceptive behaviors.ResultsModern approaches were most used by 15–19-year-olds. Between 2011 and 2017–2018, fewer educated women read a newspaper or magazine at least once a week, suggesting older women watch more TV. Over time, elderly adults utilize none of the three media at least once a week. According to the findings, elderly women are the least likely to receive weekly media coverage of their contraceptive treatments. In short, the study found that younger women utilize current contraceptive techniques, while older women may employ them less frequently, and better education significantly enhances contraceptive use, as there is a strong correlation between educational attainment and the utilization of contraception. Moreover, the results indicated that women who were not exposed to the media were less likely than those who were to use contemporary techniques.ConclusionThe report strongly recommends improving the education of disadvantaged people, particularly Bangladeshi women. To boost the nation's usage of contraceptives, women need effective health behavior education, family planning, and counseling programs.